Multi-characterization-assisted construction of the molecular structure of high-volatile bituminous coal - Xiang Feng; Youquan Dou; Yuanyuan An; Zheyao Xiong; Qingsong Wang; Tan Shi; Rudan Chen (PLoS ONE, 2026)
Elucidating coal molecular structures is critical for studying its structure–property relationships and advancing efficient coal resource utilization. In this study, a bituminous coal (JSM_C) was selected from the coal-rich Inner Mongolia region of China as the research object. Multi-characterization technologies, including elemental analysis, 13 C solid-state nuclear magnetic resonance spectroscopy ( 13 C NMR), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS), were integrated to characterize the elemental composition, carbon skeleton, functional groups, and nitrogen species in JSM_C. The results showed that the molecular formula of JSM_C is C 176 H 128 O 19 N 2 . The carbon skeleton is centered on mono-/bi-/tricyclic aromatics connected by aliphatic or oxygen-linked chains. The oxygen-containing functional groups are mainly phenols and ethers, while nitrogen species exist in the form of pyridine and pyrrole heterocycles. The simulated spectra of NMR and FTIR are consistent with the experimental data, confirming the reliability of the constructed structure. This study achieved the construction of complex coal macromolecules from the specific mine through “characterization analysis-model construction-simulation verification,” providing a feasible paradigm for coal molecular structure research. It also lays a molecular foundation for investigating structure-performance relationships and introducing related algorithmic models in coal research.